The Proteasomal ATPases Use a Slow but Highly Processive Strategy to Unfold Proteins - Snoberger, Aaron; Anderson, Raymond T.; Smith, David M. (Frontiers in Molecular Biosciences, 2017)
All domains of life have ATP-dependent compartmentalized proteases that sequester their peptidase sites on their interior. ATPase complexes will often associate with these compartmentalized proteases in order to unfold & inject substrates into the protease for degradation. Significant effort has been put into understanding how ATP hydrolysis is used to apply force to proteins and cause them to unfold. The unfolding kinetics of the bacterial ATPase, ClpX, have been shown to resemble a fast motor that traps unfolded intermediates as a strategy to unfold proteins. In the present study, we sought to determine if the proteasomal ATPases from eukaryotes and archaea exhibit similar unfolding kinetics. We found that the proteasomal ATPases appear to use a different kinetic strategy for protein unfolding, behaving as a slower but more processive and efficient translocation motor, particularly when encountering a folded domain. We expect that these dissimilarities are due to differences in the ATP binding/exchange cycle, the presence of a trans-arginine finger, or the presence of a threading ring (i.e. the OB domain), which may be used as a rigid platform to pull folded domains against. We speculate that these differences may have evolved due to the differing client pools these machines are expected to encounter.